MENGGAMBAR BEBAS SEBAGAI MEDIA EKSPRESI VISUAL PADA ANAK KELAS V SD NEGERI 4 KUTOHARJO KABUPATEN REMBANG - Yunita Dwi Selviana; Singgih Adhi Prasetyo; Ferina Agustini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by differences in students' abilities, experiences, and confidence levels in drawing activities, where drawing in elementary schools is often still bound by certain rules such as following teacher-given themes or imitating objects, which makes some students less confident and less free to express ideas through drawings. This study aims to describe the stages of free drawing as a medium of visual expression and the results of students’ drawings. This research uses a descriptive qualitative approach with 29 fifth-grade students of SD Negeri 4 Kutoharjo, Rembang Regency as subjects. Data collection techniques include observation, interviews, and documentation. The results show that the stages of free drawing are carried out through three processes, namely drawing based on initial abilities, developing themes based on personal ideas and experiences, and obtaining visual references as idea triggers, while the results of students' drawings show various themes such as natural scenery, culture, flora, fauna, buildings, surrounding objects, geometric shapes, and characters, and visually reflect elements such as line, shape, color, and composition, as well as containing stories that describe students’ experiences, imagination, and feelings. In general, free drawing activities provide space for students to express their ideas, imagination, and feelings more freely based on their experiences and individual characteristics.